Effect of Mold Flux Containing Ce2O3 on the Contents of Aluminum, Silicon, and Titanium in Incoloy825 Super Alloy - Geng Xin; Boyang Li; Zhouhua Jiang; Hou Yu (Advances in Materials Science and Engineering)
The effect of mold flux containing Ce2O3 on the contents of aluminum, silicon, and titanium in Incoloy825 super alloy was investigated based on the slag-steel interfacial chemical reaction experiment between mold flux and alloy. Firstly, the activity model of the CaO-SiO2-Al2O3-Na2O-MgO-CaF2-Ce2O3 slag system was established according to the ion and molecule coexistence theory (IMCT), and the calculation results show that with the increase of Ce2O3 content in the mold flux, the activity of Al2O3 decreases significantly and the activity of SiO2 decreases and gradually tends to 0. Secondly, thermodynamic calculations of the slag-steel interfacial chemical reaction revealed that the main chemical reaction in this study system is [Ti] + (SiO2) = [Si] + (TiO2). With the increase of Ce2O3 content in the mold flux, the slag-steel interfacial chemical reaction is weakened and the oxidation of Al and Ti in steel is inhibited. Finally, the results of slag-steel reaction experiment show that the increase rate of Al content increases from 1.03% to 10.31%, the increase rate of Si content decreases from 55.95% to 31.25%, and the oxidation rate of Ti content decreases from 33.27% to 20.00% when Ce2O3 content in the mold flux increases from 0% to 15% and the slag-steel reaction for 40 mins.